Proud of you, so act for you? The role of national pride in promoting individual pro-environmental tendencies - Wang, Pengcheng; Dong, Zhiqiang; Cai, Shenggang; Xiao, Min (Frontiers in Environmental Science, 2023)
The promotion of pro-environment behaviors is important for achieving national and global environmental protection goals. However, there is a gap between the government’s environmental will and the people’s pro-environmental tendencies. National pride has been identified as a critical pathway to achieving individual behaviors desired by the government. Here, we investigate the role of national pride in promoting individuals’ pro-environmental tendencies (PET). A large-scale survey and two experiments in the Chinese context were conducted to investigate the relationship between national pride and PET and the tools for promoting national pride and PET. The results show that national pride is positively associated with individuals’ PET. Priming with national achievements promotes individuals’ PET by inspiring their national pride. Both political-economic achievements and historical-cultural achievements can inspire Chinese people’s national pride, but political-economic achievements are more effective. Moreover, priming national pride combined with highlighting national environmental norm information could more effectively increase PET. Our findings illuminate the relationship between individuals’ national pride and PET, suggesting a potential means for translating national environmental will into individuals’ pro-environmental actions.